Possible origin of B chromosome in Dichotomius sericeus (Coleoptera) - Amorim, Igor Costa; Milani, Diogo [UNESP]; Cabral-de-Mello, Diogo Cavalcanti [UNESP]; Rocha, Marilia Franca; Moura, Rita Cassia (Canadian Science Publishing, Nrc Research Press, 2016)
B chromosomes have so far been described in about 80 species of Coleoptera, mainly using conventional staining analysis. In this study, 152 individuals of the dung beetle Dichotomius sericeus (Coleoptera), collected from three isolated geographical areas in the State of Pernambuco, Brazil, were analyzed to determine the frequency, prevalence, distribution, meiotic behavior, and possible B chromosome origin. The cytogenetic analysis consisted of conventional staining, C-banding, triple fluorochrome staining (CMA3/DA/DAPI), and fluorescent in situ hybridization using ribosomal DNAs (rDNAs) and H3 histone gene as probes, as well as microdissection and chromosome painting of the B chromosome. The B chromosomes were detected in all populations analyzed. Analysis revealed the heterochromatic nature and the presence of G+C-rich blocks and 18S rDNA on the B chromosome. FISH with DNA from microdissected B chromosome painted the entire extension of the B chromosome for all populations, besides the pericentromeric regions of all the autosomes, as well as the X chromosome. Finally, cross-hybridization in nine related species of Dichotomius using the microdissected B chromosome as probe did not reveal any hybridization signal. The results suggest an intraspecific and monophyletic origin for B chromosomes in D. sericeus, probably from the second or third autosomal pair.
Keywords: chromosome painting; chromosome evolution; histone; rDNA